Teknologi Dekafeinasi Biji Kopi Sederhana Untuk Industri Kecil di Desa Sriwulan Kabupaten Kendal - Putri, Radenrara Dewi Artanti; Arfriandi, Arief; Nurmasitah, Sita; Megawati, Megawati; Pangestu, Indra Sakti; Salsabila, Luvena; Sitanggang, Desy Manuela Boru (Politeknik ATI Padang, 2024)
Coffee is one of the leading commodities in Sriwulan Village, Kendal. This certainly has great potential for the economy to grow the MSME movement in the local community. The superior product that has been marketed is ground coffee in general which has quite a high caffeine content. Coffee with low caffeine content is currently a trend on the market and is popular with many health-conscious people. At the industrial level, widely developed decaffeination processes often use imported technology, both at the hardware and software level, which results in the price of low-caffeinated coffee still being relatively high. Limited public access to information regarding decaffeination techniques in coffee means consumers of low-caffeine coffee are willing to pay high prices to get a product that suits their tastes. The process of decaffeinating coffee beans can add value to the selling value of Indonesian coffee commodities, especially in Sriwulan Village, Kendal Regency. The aim of this service activity is to provide education and equipment assistance to the Sriwulan Village community about low-caffeine coffee and its production process to more attractive packaging, so that partner communities can take advantage of this to improve the economy of Sriwulan Village. The method of implementing this activity is carried out through the survey stage, training and monitoring stages. The implementation stage is carried out by processing coffee beans that have been peeled and dried in the sun, then steamed at a temperature of 100oC for 90 minutes. Coffee beans that have been steamed are ready to be dried and roasted according to the steps usually carried out by coffee farmers in Sriwulan Village. This service succeeded in increasing the understanding and interest of coffee producers in Sriwulan Village to develop low-caffeine coffee products. The program implemented can produce coffee beans that experience a reduction in caffeine levels of up to 80.8% after testing caffeine levels.